Common goal areas in the treatment of upper limb spasticity: a multicentre analysis. (June 2016) - Ashford, Stephen; Fheodoroff, Klemens; Jacinto, Jorge; Turner-Stokes, Lynne
Objective: We aimed to develop a goal classification of individualised goals for spasticity treatment incorporating botulinum toxin intervention for upper limb spasticity to under-pin a more structured approach to future goal setting. Design: Individualised goals for spasticity treatment incorporating botulinum toxin intervention for upper limb spasticity ( n =696) were analysed initially from four studies published in 2008-2012, spanning a total of 18 centres (12 in the UK and 6 in Australia). Goals were categorised and mapped onto the closest matching domains of the WHO International Classification of Functioning. Confirmatory analysis included a further 927 goals from a large international cohort study spanning 22 countries published in 2013. Results: Goal categories could be assigned into two domains, each subdivided into three key goal areas: Domain 1: symptoms/impairment n =322 (46%): a. pain/discomfort n =78 (11%), b. involuntary movements n =75 (11%), c. range of movement/contracture prevention n =162 (23%). Domain 2: Activities/function n =374 (54%): a. passive function (ease of caring for the affected limb) n =242 (35%), b active function (using the affected limb in active tasks) n =84 (12%), c. mobility n =11 (2%). Over 99% of the goals from the large international cohort fell into the same six areas, confirming the international applicability of the classification. Conclusions: Goals for management of upper limb spasticity, in worldwide clinical practice, fall into six main goal areas.